The Role of Artificial Intelligence in Handling Discrimination of BPJS Patients in Health Services - Nucky Indra Praja (Publikasi Indonesia, 2024)
Health services must be oriented towards meeting consumer demands and expectations, which are closely related to service quality. However, there are still problems in its implementation, such as discrimination against BPJS patients, who often get different treatment compared to non-BPJS patients, both in service quality and access to health facilities. According to Article 28H Paragraph (1) of the 1945 Constitution, everyone has the right to a prosperous life and decent health services. The objective of this study is to identify the role of artificial intelligence in reducing and preventing discrimination against BPJS patients in Health services, and to analyse how legal regulations can support the application of AI to ensure the creation of fair and non-discriminatory health services. [Methods] The research method used is normative juridical, using a statutory approach and an analytical approach. The results show that AI has significant potential in detecting and preventing discrimination, for example through algorithms that monitor the treatment of patients in real-time. However, the application of AI must be supported by a clear legal framework to ensure that the use of this technology does not exacerbate inequality, but rather supports equitable access to health services. The conclusion of this study is that artificial intelligence can be an effective solution in addressing discrimination of BPJS patients, as long as it is integrated with policies and regulations that protect the rights of patients, as well as ensuring oversight and accountability on the part of healthcare providers.